Sex Differences in Vascular Compliance in Normal-Weight but Not Obese Boys and Girls: The Effect of Body Composition. (11th March 2012) - Tryggestad, Jeanie B.; Thompson, David M.; Copeland, Kenneth C.; Short, Kevin R.
Abstract : Objectives . To determine the effect of sex and obesity on vascular function in children and explore potential mechanisms that account for differences in vascular function. Methods . Participants were 61 (30 boys) normal-weight (BMI 25–75% ile for age and sex) and 62 (30 boys) obese (BMI ≥ 95% ile) children of ages 8–18 years. Measurements of large and small artery elastic index (LAEI and SAEI, resp.) and reactive hyperemia index (RHI) were obtained at rest, along with anthropometric and biochemical information. Results . In normal-weight children, LAEI was 16% higher in males than females (P = 0.04 ) with a similar trend for SAEI (13% higher in males, P = 0.067 ). In obese children, no sex-related differences in vascular measures were observed. In multivariable models, sex differences in arterial compliance were explained by higher lean mass in normal-weight boys. Fat mass predicted LAEI and SAEI in both normal-weight and obese females, but fat mass predicted arterial compliance in boys when fat mass exceeded 24 kg (37% of the sample). Conclusions . Normal-weight males have higher arterial compliance than normal-weight females due to increased lean mass, but sex-related differences were not observed among obese children due to a lack of sex-related differences in lean or fat mass.